Instructional design for action learning Geri McArdle - McArdle, Geri E. H (American Management Association, 2011)
The book walks you through the six fundamental steps necessary for superior instructional design, from defining the need for training, to planning, to delivery, to evaluation. Filled with numerous examples of active, thought-stimulating learning te